Central counterparty exposure in stressed markets - HUANG, Wenqian (Institutional Knowledge at Singapore Management University, 2021)
Time is valuable, particularly in stressed markets. Because central counterparties (CCPs) have become systemically important, we need to understand the dynamics of their exposure toward clearing members at high frequencies. We track such exposure and decompose it, yielding the following insights. The composition of CCP exposure is fundamentally different in the tails. At extreme levels or during rapid increases, there is elevated crowding. This is the result of clearing members all concentrating their positions on a single security or a particular portfolio, which is desirable if motivated by hedging but worrying if due to speculation.